Clinical case: idelalisib-induced immunoglobulin flare. (4th July 2017) - Novak, Jan; Havrda, Martin; Gaherova, Lubica; Spicka, Jan; Kozak, Tomas
Abstract: IgM flare is a transient, treatment-induced, increase of monoclonal IgM levels in lymphoplasmacytic lymphoma/Waldenström macroglobulinemia (LPL/WM) patients. Until recently this phenomenon was observed in patients treated with Cladribine and Rituximab. Here we report a case of a heavily pretreated chronic lymphocytic leukemia patient with an atypically high immunoglobulin production who developed clinically significant immunoglobulin flare following Idelalisib treatment.